(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
This case report describes the management of a 25-year-old female patient having Class I malocclusion with maxillary and mandibular crowding.The treatment include extracting the lower right central incisor and comprehensive edgewise orthodontic therapy. We decided extraction of lower right central incisor because it was broken down crown and also for shortening the treatment time and easy correction of mandibular crowding. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15988 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 25-28